2012
DOI: 10.1111/j.1444-0938.2012.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Macular folds: an unusual association in topiramate toxicity

Abstract: We report two uncommon cases of acute onset myopia with macular folds following use of topiramate. A 25-year-old woman, with no prior history of glasses, taking topiramate for recurrent headaches, presented with decreased vision. On examination, she was found to have a refractive error of -5.00 DS in both eyes and intraocular pressure of 10 mmHg and 6 mmHg in the right and left eyes, respectively. She had closed angles on gonioscopy, ciliary effusion on ultrasonic biomicroscopy with inner limiting membrane fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…1 ]. [ 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 ]…”
Section: Resultsunclassified
“…1 ]. [ 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 ]…”
Section: Resultsunclassified
“…It has been reported in Vogt Koyanagai Harada's syndrome, and even in the literature that this exacerbation period of the syndrome may be a leading indicator [22]. In some patients using topiramate, it has been reported that reversible macular folds can be the observed [23]. In diabetic retinopathy cases, some CF cases have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Both women presented with macular folds associated with angle-closure glaucoma. The symptoms disappeared after discontinuation of the drug (Kumar et al, 2006).…”
Section: Systemic Agents and Ocular Toxicitymentioning
confidence: 98%